The complete F-type mitochondrial genome of Chinese freshwater mussel Anodonta euscaphys. (3rd July 2016) - Xue, Ting; Chen, Meiling; Wang, Guiling; Han, Zhenyong; Li, Jiale
Abstract: Anodonta euscaphys is the endemic species of freshwater mussel in China. The complete F-type mitochondrial genome of the A. euscaphys is amplified and analyzed in this study. It is 15, 741 bp in length. The base composition of the genome with A + T bias is 64.78%. There are 24 noncoding regions found throughout the mitogenome of A. euscaphys, ranging in size from 3 to 302 bp, the largest of which was between ND2 and tRNA Glu . The phylogenetic tree based on 22 mitogenome, including 16 F-type freshwater mussels, 2 M-type freshwater mussels and 4 marine mussels were analyzed in our study, the results showed that the F-type and the M-type of the freshwater mussels were clustered respectively, the A. euscaphys was clustered with Anodonta family species firstly, and it was the closest to the Anodonta arcaeformis in our analysis.